Long Non-Coding RNA MDFIC-7 Promotes Chordoma Progression Through Modulating the miR-525-5p/ARF6 Axis - Zhang, Kai; Liu, Zixiang; Wang, Zhidong; Zhou, Zhangzhe; Shao, Xiaofeng; Hua, Xi; Mao, Haiqing; Yang, Huilin; Ren, Ke; Chen, Kangwu (Frontiers in Oncology, 2021)
Background Chordoma, an extremely rare malignant tumor, remains difficult to be cured because of its strong local invasiveness and high recurrence rate. Long non-coding RNAs (lncRNAs) have been demonstrated to play multiple roles in various cancers. The purpose of this study was to investigate the modulatory function of lncRNA MDFIC-7 in chordoma and to elucidate its underlying mechanisms. Methods Quantitative real-time polymerase chain reaction was performed to detect the expression of lncRNA MDFIC-7 in tumor tissues and adjacent nontumorous tissues collected from 15 chordoma patients, as well as in chordoma cell lines. Gene silencing and overexpression experiments were carried out by RNA interference and lentiviral transduction. The effect of lncRNA MDFIC-7 on the proliferation of chordoma cells was evaluated by cell counting kit-8 assay, colony formation assay and xenograft tumor experiments. RNA immunoprecipitation and dual luciferase reporter assays were conducted to evaluate the binding between lncRNA MDFIC-7 and miRNA-525-5p and the interaction between miR-525-5p and the 3′ untranslated region of ADP-ribosylation factor 6 (ARF6) mRNA. The glycolytic capacity and mitochondrial function of chordoma cells were measured by the Seahorse Bioscience XF96 Extracellular Flux Analyzer. Results The expression of lncRNA MDFIC-7 was higher in chordoma tumor tissues than in adjacent non-tumor tissues. Downregulation of lncRNA MDFIC-7 reduced colony formation and cell proliferation in chordoma cells and decreased xenograft tumor growth in a nude mouse model. Moreover, lncRNA MDFIC-7 knockdown attenuated the Warburg effect in chordoma cells and xenograft tumors. LncRNA MDFIC-7 knockdown elevated miR-525-5p levels and decreased ARF6 expressions. Overexpression of ARF6 reversed the inhibitory effect of lncRNA MDFIC-7 knockdown on cell proliferation and the Warburg effect in chordoma cells and xenograft tumors. Mechanistically, lncRNA MDFIC-7, as a molecular sponge of miR-525-5p, negatively regulated miR-525-5p expression and promoted the gene expression of ARF6, a miR-525-5p target. Conclusion Our findings demonstrate that lncRNA MDFIC-7 acts as a molecular sponge to competitively bind to miR-525-5p and promote expression of ARF6. The lncRNA MDFIC-7/miR-525-5p/ARF6 axis regulates chordoma progression and the Warburg effect in chordoma, suggesting that lncRNA MDFIC-7 and miR-525-5p could be promising therapeutic targets for the treatment of chordoma.